Disentangling the trajectories of maternal depressive symptoms and partnership problems in the transition to parenthood and their impact on child adjustment difficulties - Ray, Jana; Stürmlinger, Linda Luisa; Krause, Mischa von; Lux, Ulrike; Zietlow, Anna-Lena (Development and psychopathology, 2023)
Maternal perinatal depression (PND) and partnership problems have been identified to influence the development of later child adjustment difficulties. However, PND and partnership problems are closely linked which makes it difficult to draw conclusions about the exact transmission pathways. The aim of the present study was to investigate to what extent PND symptoms and partnership problems influence each other longitudinally and to examine the influence of their trajectories on child adjustment difficulties at the age of three. Analyses were based on publicly available data from the German family panel “pairfam”. N = 354 mothers were surveyed on depressive symptoms and partnership problems annually from pregnancy (T0) until child age three (T4). Child adjustment difficulties were assessed at age three. Results of latent change score modeling showed that partnership problems predicted change in PND symptoms at T0 and T3 while PND symptoms did not predict change in partnership problems. Child adjustment difficulties at age three were predicted by PND symptoms, but not by partnership problems. Partnership problems predicted externalizing, but not internalizing symptoms. Results underline the effects of family factors for the development of child adjustment difficulties and emphasize the importance of early interventions from pregnancy onwards